Mental health, family roles and employment status inside and outside the household in Spain - Jorge Arias-de la Torre; Antonio J. Molina; Tania Fernández-Villa; Lucía Artazcoz; Vicente Martín (Gaceta Sanitaria, 2019)
Objective: To document the prevalence of poor mental health by gender and social class, and to analyze if poor mental health is associated with the family roles or the employment status inside and outside the household. Method: A cross-sectional study based on a representative sample of the Spanish population was carried out (n = 14,247). Mental health was evaluated using GHQ-12. Employment status, marital status, family roles (main breadwinner and the person who mainly carries out the household work) and educational level were considered as explanatory variables. Multiple logistic regression models stratified by gender and social class were fitted and adjusted odds ratios (aOR) were obtained. Results: Gender and social class differences in the prevalence of poor mental health were observed. Unemployment was associated with higher prevalence. Among men the main breadwinner role was related to poor mental health mainly in those that belong to manual classes (aOR = 1.2). Among women, mainly among nonmanual classes, these problems were associated to marital status: widowed, separated or divorced (aOR = 1.9) and to dealing with the household work by themselves (aOR = 1.9). Conclusions: In Spain, gender and social class differences in mental health still exist. In addition, family roles and working situation, both inside and outside the household, could constitute a source of inequalities in mental health. Resumen: Objetivo: Conocer la prevalencia de mala salud mental por sexo y clase social, y analizar si la salud mental se relaciona con los roles familiares y la situación laboral fuera y dentro del hogar. Método: Se realizó un diseño transversal basado en una muestra representativa de la población española (n = 14.247). La salud mental se evaluó mediante el GHQ-12. Se consideraron como variables explicativas la situación laboral, el estado civil, el rol familiar (sustentador principal y persona que realiza el trabajo doméstico) y el nivel de estudios. Se ajustaron modelos de regresión logística estratificados por sexo y se obtuvieron las odds ratio ajustadas (ORa). Resultados: Se observaron diferencias en la prevalencia de mala salud mental por sexo y clase social. El desempleo se asoció con mayor prevalencia. En hombres pertenecientes a clases menos favorecidas, el rol de sustentador principal se relacionó con mala salud mental (Ora = 1,2) En mujeres que pertenecían a clases más favorecidas, el estado civil viuda, separada o divorciada (ORa = 1,9) y realizar el trabajo doméstico solas (ORa = 1,9) se relacionaron con mala salud mental. Conclusiones: En España, en salud mental continúa habiendo diferencias de sexo y clase social. Además, el rol familiar y la situación laboral fuera y dentro del ámbito doméstico podrían constituir también una fuente de desigualdad en salud mental. Keywords: Mental health, Occupational health, Gender, Socioeconomic factors, Health survey, Palabras clave: Salud mental, Salud laboral, Género, Factores socioeconómicos, Encuestas de salud